Estimating carbon sequestered in the cryptosepalum forest in Mwinilunga district of North-western Province, Zambia - Kambayi, Martin (Stellenbosch : Stellenbosch University, 2017)
Thesis (MScFor)--Stellenbosch University, 2017.